Comparative Analysis of the Vibrational Response of Different Main Rotor Blades of a Homemade Helicopter - Tangka, Julius K.; Ngah, John Ngangsi; Kuaban, Godlove Suila; Evina, Mathias N. W. (European Journal of Applied Sciences, 2022)
This paper investigates the dynamics of homemade helicopter wooden and aluminum sheet rotor blades. The rotors are articulated and their blades are rigid. The main rotor implementation takes into account flap, lag, and feather degrees of freedom for each of the equispaced blades as well as their dynamic couplings. Transmitted vibrations due to the rotating rotor blades on the body structure (fuselage) are studied. This work presents an aerodynamic model of main rotor blades that allows us to analyse vibrational transmissions on the fuselage (body) of the craft. Vibrations in helicopters is a common problem which involves complex interactions between the inertial, structural and aerodynamic loads, especially in homemade helicopters. The major source of vibrations in helicopters is the main rotor. The efficiency and stability of the main rotor blades is determined by the magnitudes of the predominant frequencies they produce. These vibrations affect the functionality, durability of the engine component parts, increase maintenance frequency (cost), and cause structural failures. The aerodynamic model has been built up using blade element theory. The aerodynamic load creates vibrations on the homemade helicopter and these are analyzed on the fuselage by using a short time Fourier transform that brings out the vibrational spectrum. The results of the analysis serve as a reference to characterize the stability and efficiency of homemade main rotor blade profiles.